Emerging Role of Mechanical Forces in Cell Fate Acquisition - Alvarez, Yanina; Smutny, Michael (Frontiers in Cell and Developmental Biology, 2022)
Mechanical forces are now recognized as key cellular mechanisms that together with genetic and cellular signals physically shape tissues and organs during development. Increasing efforts are aimed towards understanding the less explored role of mechanical cues in controlling cell fate decisions in embryonic development. Here we discuss recent examples of how differential forces feedback into cell fate specification and tissue patterning. In particular, we focus on the role of actomyosin-contractile force generation and transduction affecting tissue morphogenesis and cell fate regulation in the embryo.